Children Songs as A Learning Media Used in Increasing Motivation and Learning Student in Elementary School - Ardian Arief; Faris Isnan (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2020)
Motivation can be a driving force within students that gives rise to learning activities, which ensures continuity of learning activities and which gives direction to learning activities so that the desired goals of the learning subject can be achieved. Students who have strong motivation will have much energy to do learning activities. The results of learning activities will also be optimal if there is the right motivation—media in education functions as a means to achieve learning objectives. Therefore, the information contained in the media must be able to engage students, both mentally and in the form of real activities, so that learning can occur. The use of media in learning in elementary schools can affect student motivation, and the findings evidence this. Differences in learning motivation in thematic learning between the experimental class taught using the learning media of children's songs and the control class taught using classical music learning media, which is seen from the average score of the experimental class at 77.35 and the control class 68.00. From these results, the average experimental class was higher than the control class (77, 35 68.00).